Socio-Economic Life of Traditional Woven Fabric Articles In Lakekun Utara Village, Kobalima Sub-District, Malaka Regency - Hildigardis M.I. NAHAK; Herman Y. UTANG; Balkis Soraya TANOF (PT Keberlanjutan Strategis Indonesia, 2023)
Traditional weaving is generally inherited from the ancestors and is also part of the socio-economic life of the craftsmen in North Lakekun Village. They work like this almost every day, but what is unique is that the traditional woven fabric craftsmen in North Lakekun Village do not weave for sale. Instead, they weave to store it while waiting for a celebration. This study used a qualitative approach and a total of 45 informants with qualitative and quantitative data. The data collection techniques in this study were observation, qualitative interviews and qualitative documents. The data that has been collected is then analyzed using analytical techniques; data collection, data reduction, data display, and conclusion drawing and verification. The results of the study found that the socio-economic life of traditional woven fabric craftsmen in North Lakekun, Kobalima District, Malacca Regency was found from the side; (a) the level of income is quite good because they rely on agricultural and livestock products, (b) the level of education is relatively low, while in terms of (c) health, the craftsmen use health cards such as BPJS for free medical treatment, some seek and use traditional medicine whereas for (d) the condition of the houses of the traditional woven cloth craftsmen there in general, on average, they have decent houses to live in and (e) the social relations between fellow woven cloth craftsmen there look very good.